Characterization of TIG and MIG welded Aluminium 6063 alloys. (2021) - Ramji, B.R.; Bharathi, V.; Prabhu Swamy, N.R.
Abstract: Aluminium being light weight, strong & corrosion resistant material is extensively used in transportation industries, packaging, construction and many more. Al can be alloyed with elements like silicon and magnesium to improve the properties. Though the welding of Al-alloys have several of advantages; in some cases, Al-alloys experience issues which connect the alloy content, metallurgy & the process during welding. An attempt has been made in the present investigation to carry out fusion welding for Aluminium 6063 alloys using TIG & MIG techniques. Different types of filler rods were used in TIG process and spool of alloy 6061was used in MIG welding processes. Further characterization studies were carried out to assess the BHN and tensile strength of the joints. Microstructure studies were also conducted using metallurgical microscope on TIG and MIG welded joints to assess the different zones and grain formation on the welded joints.